Estrogen and Progestin Use and the QT Interval in Postmenopausal Women - Kadish, Alan H. (Ann Noninvasive Electrocardiol, 2004)
Objective: To determine whether menopausal hormone therapy alters the QT interval in primarily healthy postmenopausal women. Background: Despite well‐known gender differences in myocardial repolarization that include a longer heart‐rate‐corrected QT interval (QT(C)) in women compared to men, the effects of menopausal hormone therapy on myocardial repolarization in women have not been well characterized. Methods: We studied 34,378 postmenopausal women participating in the dietary intervention component of the Women's Health Initiative. Cross‐sectional associations were examined to assess possible effects of estrogen + progesterone on myocardial repolarization. Women who reported that they were never treated with menopausal hormone therapy (n = 12,451) were compared to women with a past use of menopausal hormone therapy (n = 3891), currently taking unopposed estrogen therapy (n = 9987), or combined current estrogen and progesterone therapy (n = 8049). Results: Using analysis of covariance, the mean (±SEM) QT(C) interval was 423.1 ± 0.2 milliseconds (ms) in those never treated with menopausal hormone therapy, 423.9 ± 0.3 ms in past menopausal hormone therapy users, 425.6 ± 0.2 ms in those currently on estrogen alone, and 424.0 ± 0.2 ms in women currently on combined estrogen–progesterone therapy. Differences in mean QT(C) between those on estrogen alone and the other three groups were statistically significant. Comparisons of JT intervals, QT intervals, and linear corrected QT intervals among the groups yielded similar results. Conclusion: These results suggest that unopposed estrogen in menopausal women mildly prolongs myocardial repolarization, and the effect is reversed by progesterone. Whether these findings have clinical significance requires further study.